2020
DOI: 10.1111/aswp.12212
|View full text |Cite
|
Sign up to set email alerts
|

The nexus between zakat and poverty reduction, is the effective utilization of zakat necessary for achieving SDGs: A multidimensional poverty index approach

Abstract: This study develops and validates a comprehensive mechanism for evaluating the effect of zakat (obligatory alms‐giving) on reducing poverty and attaining some of the prominent Sustainable Development Goals. The study unconventionally analyzes the effect of macrolevel data on microlevel data on district level of Khyber Pakhtunkhwa, Pakistan. Microlevel data are utilized from a renowned national survey, Pakistan Social and Living Standards Measurement Survey (PSLM) from which the Multidimensional Poverty Index (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 30 publications
0
25
0
3
Order By: Relevance
“…The variables used in the study are measured as follows: different variables are used as measures of poverty in empirical studies. Headcount-based data for the poor (Omar and Inaba, 2020;Baloch et al, 2020;Kousar and Shabbir, 2021;Solarin, 2021;Ogbeide-Osaretin, 2021), income (Adekoya, 2018), infant mortality (Tsaurai, 2018;Magombeyi and Odhiambo, 2018;Khobai, 2021;Solarin, 2021), life expectancy (Magombeyi and Odhiambo, 2018;Tsaurai, 2018), multidimensional poverty index (Aziz et al, 2020;Osinubi and Olomola, 2020) and human development index (Nwani and Osuji, 2020) are used as proxy for poverty in some studies. Some other studies used per capita consumption expenditure as proxy for poverty due to the lack of data on poverty (Quartey, 2008;Odhiambo, 2009;Odhiambo, 2011;Nayasha, Gwenhure and Odhiambo, 2017;Sehrawat and Giri, 2018;Adeleye et al, 2020;Dada and Fanowopo, 2020;Garidzirai and Matiza, 2020).…”
Section: Datamentioning
confidence: 99%
“…The variables used in the study are measured as follows: different variables are used as measures of poverty in empirical studies. Headcount-based data for the poor (Omar and Inaba, 2020;Baloch et al, 2020;Kousar and Shabbir, 2021;Solarin, 2021;Ogbeide-Osaretin, 2021), income (Adekoya, 2018), infant mortality (Tsaurai, 2018;Magombeyi and Odhiambo, 2018;Khobai, 2021;Solarin, 2021), life expectancy (Magombeyi and Odhiambo, 2018;Tsaurai, 2018), multidimensional poverty index (Aziz et al, 2020;Osinubi and Olomola, 2020) and human development index (Nwani and Osuji, 2020) are used as proxy for poverty in some studies. Some other studies used per capita consumption expenditure as proxy for poverty due to the lack of data on poverty (Quartey, 2008;Odhiambo, 2009;Odhiambo, 2011;Nayasha, Gwenhure and Odhiambo, 2017;Sehrawat and Giri, 2018;Adeleye et al, 2020;Dada and Fanowopo, 2020;Garidzirai and Matiza, 2020).…”
Section: Datamentioning
confidence: 99%
“…Zakat acts as a mechanism for distributing benefits, designed to bridge the gap between the rich and the poor [31]. This mechanism increases the purchasing power of the poor and should contribute to economic growth by increasing consumer spending and aggregate demand.…”
Section: Practical Aspects Of Islamic Banking As An Institutionmentioning
confidence: 99%
“…Suprayitno et al (2017) found that zakat has a positive and significant effect on SDGs in five Malaysian states. Aziz et al (2020) found that zakat was able to reduce multidimensional poverty and made a significant contribution to several SDGs in Pakistan. That means there is no direct data collection for each mustahik of the zakat funds.…”
Section: Introductionmentioning
confidence: 99%
“…However, some empirical studies above have not discussed the role of zakat fund management carried out by LAZ in realizing SDGs number 1 (no poverty). In addition, the data used are still macroeconomic, such as the human development index in Malaysia (Suprayitno et al, 2017) and the multidimensional poverty index in Pakistan (Aziz et al, 2020). Moreover, research conducted by Abduh (2019); Amalia et al (2020); Dembele and Bulut (2021) is still at the conceptual level about the role of zakat and the Islamic social fund.…”
Section: Introductionmentioning
confidence: 99%